Scaling-Up of Bulk β-Ga2O3 Single Crystals by the Czochralski Method. (1st September 2016) - Galazka, Zbigniew; Uecker, Reinhard; Klimm, Detlef; Irmscher, Klaus; Naumann, Martin; Pietsch, Mike; Kwasniewski, Albert; Bertram, Rainer; Ganschow, Steffen; Bickermann, Matthias
Abstract : We present a new approach for scaling-up the growth of β-Ga2 O3 single crystals grown from the melt by the Czochralski method, which has also a direct application to other melt-growth techniques involving a noble metal crucible. Experimental and theoretical results point to melt thermodynamics as the crucial factor in increasing the volume of a growing crystal. In particular, the formation of metallic gallium in the liquid phase in large melt volumes causes problems with crystal growth and eutectic or intermetallic phase formation with the noble metal crucible. The larger crystals to be grown the higher oxygen concentration is required. The minimum oxygen concentration ranges from about 8 to 100 vol.% for 2 to 4 inch diameter cylindrical crystals, challenging the use of iridium crucibles in a combination with such high oxygen concentrations. A specific way of oxygen delivery to a growth furnace with the iridium crucible allows to minimize the formation of metallic gallium in the melt and thus obtaining large crystal volumes while decreasing the probability of the eutectic formation.